Effects of gut microbiota-derived short-chain fatty acids on cognitive impairment: An in-silico study - Hai Duc Nguyen; Giang Huong Vu; Woong-Ki Kim (Aspects of Molecular Medicine)
Increasing evidence suggests that gut microbiota-derived metabolites affect cognitive function, but the underlying molecular mechanisms remain unclear. In this study, mechanisms of cognitive dysfunction that can be targeted by acetic acid and butyric acid were analyzed using literature review, Metascape, Mienturnent, Passonline, and WissADME. We found that acetic acid and butyric acid may regulate important genes (PPARG, CASP3, IL1B, SOD2, and TNF) that protect against cognitive decline. We also found microRNAs (hsa-miR-17-5p and hsa-miR-20a-5p) and transcription factors (RELA and NFKB1) that play a critical role in this protective mechanism. The AGE-RAGE signaling pathway and apoptosis pathways also emerged as crucial to understanding the underlying pathophysiological mechanisms. Our findings are further supported by the physicochemical properties and pharmacokinetic profiles of acetic acid and butyric acid, which demonstrate remarkable intestinal absorption, ability to penetrate the blood-brain barrier, and non-inhibition of CYP450 enzymes. Our study provides further evidence of the therapeutic potential of butyric acid in managing cognitive impairment, including its anti-inflammatory properties, stimulation of insulin synthesis, and regulation of lipid metabolism. We also identified several promising treatments for cognitive impairment, including miRNA sponges, mesalazine, omega-3 fatty acids, pomalidomide, and andrographolide. Focused investigations into the apoptosis and AGE-RAGE signaling pathways, miRNA sponges, promising drugs, and the role of gut microbiota in cognitive function are warranted.